Synergistic nexus among energy security, energy equity and net electricity regions: Optimizing renewable energy integration and demand response for electrical supply systems - Jiang Wu; Yang Zhang; Akhtar Khan (Energy Strategy Reviews)
This study optimizes a local renewable electricity supply system to integrate demand response tactics for power-intensive industry activities. We use a multi-phase optimization framework to design demand response scheduling for continuous production and identify the best configuration for a local energy generating and storage system. Our main goals are to reduce overall expenses and lessen the impact of global warming. Important elements, including electric batteries, local solar and wind power generation, and intraday and day-ahead electricity trading, are all thoroughly examined in the study. The results show that, although at a significant increase in cost, adding a battery system has the potential to lower emissions and enable large-scale market electricity trading. To attain ecological and economic sustainability within the environment, this research emphasizes optimizing industrial processes. It also highlights the value of demand response methods and the integration of renewable energy in reducing the effects of climate change. The results show that the systems of demand response, integrating the usage of some renewable energy types, can significantly contribute to improved ecological and economic performance in manufacturing plants. Such research also points to the need to guard policy environments that facilitate the deployment of RE and efficient AES infrastructures to support organizations’ sustainable industrial transformation.